Madheshi Contribution in Nepali Education: Empowering Minds and Transforming Communities - Thakur, Rashmi; Thakur, Gopal Kumar; Chhetri, Surya; Jha, Tulika (International Research Journal of Parroha, 2023)
This study delves into the experiences of Madhesi community origin contribution, condition and conviction in Nepali Education with a view to empowering minds and transforming communities. With a view access the better opportunities for job and the inadequate educational infrastructure across the country, a significant number of Madhesi teachers and students are compelled to seek job and higher education in Kathmandu. However, there are instances where Madhesis are still mistaken as Indians and face discrimination in their non-native regions. In this study, we aim to uncover the feelings and experiences of Madhesi teachers and students in Kathmandu. The research employed qualitative approaches as one to one personal discussion. The responses gathered were analyzed using the theory of stigma and social interactionism developed by Erving Goffman. By examining their accounts, this research sheds light on the contribution, condition and emotional challenges faced by Madhesi due to the stigma and stereotypical remarks directed at them by their peers.